Edukasi Kesehatan dalam Meningkatkan Kepatuhan Minum Obat pada Lansia Hipertensi - Ni Wayan Putriana Dewi Agustina; Astuti Yuni Nursasi; Henny Permatasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to get an overview of health education effectively used to increase adherence to antihypertensive medication in elderly hypertensive patients. The research method used in this study was a systematic review using the ClinicalKey Nursing, EBSCOhost, Proquest, Scopus, Taylor & Francis database. Research results: Various structured health education methods using interactive methods, two-way communication accompanied by demonstrations, and various exciting media according to the target age can help improve adherence to medication in the elderly. Education can also be provided face-to-face with health workers, indirectly by telephone or empowering cadres, group education, individual education, and education in combination with other interventions. In conclusion, increasing elderly knowledge about hypertension requires structured health education using Roy's Health Belief Model and Adaptation Model approaches to improve adherence to hypertension treatment in the elderly Keywords: Health Education, Hypertension, Elderly, Medication Compliance